PARLIAMENTARY OVERSIGHT OF EXTRACTIVE INDUSTRIES - Olaore, Oladeji; Stapenhurst, Rick (Journal of Anti-Corruption Law, 2023)
Africa has experienced a boom in extractive industries since the beginning of this century. Extractive companies often are exposed not just to government patronage, but also to requests to consider local third-party agents, vendors or applications for employment. But is corruption a necessary evil? While there is consensus that multi-faceted strategies are required to curb corruption, heretofore there has been little research on how legislative oversight can help reduce corruption in general and on legislative oversight of corruption in the extractive sector in particular.